2013
DOI: 10.1007/s00392-013-0609-7
|View full text |Cite
|
Sign up to set email alerts
|

Drug-coated balloons for treatment of coronary artery disease: updated recommendations from a consensus group

Abstract: DCB allow for local drug delivery in endovascular therapy leaving no permanent implant behind.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
137
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 170 publications
(147 citation statements)
references
References 69 publications
2
137
0
Order By: Relevance
“…11 Furthermore, the use of PCB as standalone therapy represents the most rigorous approach to establish the concept of leaving nothing behind. 12,13 However, in coronary artery disease, the combination of PCB and baremetal stents turned out to be inferior to current generation limus-eluting stents. [14][15][16] Furthermore, conflicting data have been reported for PCB in the treatment of below the knee disease.…”
mentioning
confidence: 99%
“…11 Furthermore, the use of PCB as standalone therapy represents the most rigorous approach to establish the concept of leaving nothing behind. 12,13 However, in coronary artery disease, the combination of PCB and baremetal stents turned out to be inferior to current generation limus-eluting stents. [14][15][16] Furthermore, conflicting data have been reported for PCB in the treatment of below the knee disease.…”
mentioning
confidence: 99%
“…Overall results were at least comparable with DES treatment. In the larger subgroup of patients treated according to the German consensus recommendations [13,19] we found unexpected low restenosis and reocclusion rates exceeding the results described with DES. Improvement of angina was impressive as well.…”
mentioning
confidence: 73%
“…In native coronary artery lesions and in-stent restenosis (ISR) this approach leads to an extremely low restenosis and an almost zero percent thrombosis rate [10][11][12], thus obviating the need for prolonged dual antiplatelet therapy (DAPT). Four weeks of DAPT is sufficient after DCB [13] compared to six to twelve months after DES [14]. Also, a DCB approach without foreign body implantation gives the vessel the opportunity to remodel positively.…”
Section: Commentarymentioning
confidence: 97%
“…Clinically, the safety and efficacy profile of PCB was originally tested in the setting of coronary BMS‐ISR 3, 19, 20. In PERVIDEO registry study, 6‐month follow‐up showed the safety and feasibility of lutonix PCB in BMS‐ISR, and a certain biological effect as indicated by very low LLL (unpublished data, presented at TCT 2010 by Laura Mauri, MD).…”
Section: Discussionmentioning
confidence: 99%